Pharmacokinetic Properties of Three Forms of Vaginal Progesterone Administered in Either Single Or Multiple Dose Regimen in Healthy Post-menopausal Chinese Women - Wu, Guolan; Chen, Junchun; Hu, Xingjiang; Zhou, Huili; Liu, Jian; Lv, Duo; Wu, Lihua; Shentu, Jianzhong (Frontiers in Pharmacology, 2017)
Objective：A generic vaginal progesterone gel has recently been developed in China. Little is known about its pharmacokinetic properties in Chinese subjects. The purpose of our study was to investigate the pharmacokinetics of three forms of vaginal progesterone gel (test formulations at 4% and 8% strength vs. a reference formulation: Crinone 8%) in Chinese healthy postmenopausal women. Methods: This study consisted of two parts study. The part 1 study was a single-center, open-label, 3-period study. 12 healthy postmenopausal women were to evaluate the safety and pharmacokinetics of 45 mg vaginal progesterone gel (Test 4%) following single dose and multiple doses administered once every other day (q.o.d.) for 6 times or once daily (q.d.) for 6 days. The part 2 study was a randomized, open-label, 3-stage crossover study. 12 postmenopausal women received 90 mg vaginal progesterone gel (Test 8%) or 90 mg Crinone (Reference 8%) following single dose and multiple doses (q.o.d. or q.d.). Plasma concentrations of progesterone were measured up to 72 hours by using a validated LC-MS/MS method. The primary pharmacokinetic parameters, maximum plasma concentration (Cmax) and area under the plasma concentration–time curve (AUC) from time zero to last measurable concentration (AUC0-t ) and extrapolated to infinity (AUC0−∞) were compared by an analysis of variance using log-transformed data. Results: Totally 24 subjects were enrolled in and completed the study. Following single dose, The geometric mean Cmax values for Test 4%, Test 8%, and Crinone 8% were 6.35, 10.34, 10.45 ng/mL, and their geometric mean AUC0–t (AUC0–∞) were 113.73 (118.00), 169.39(173.98), and 190.07 (201.13) ng•h/mL, respectively. The mean T1/2 values of progesterone were 11.00, 10.92, and 11.40 h, respectively. For 8% test formulation vs. reference, the 90% CIs of the least squares mean test/reference ratios of Cmax, AUC0–t, and AUC0–∞ were 78.32% to 124.85%, 54.31% to 146.24%, and 53.64% to 137.75%, respectively. The most frequent adverse events were increased vaginal secretions, most of which were of mild intensity and considered related to treatment. Conclusion: Results with single and multiple doses of vaginal progesterone gel suggest similar pharmacokinetics properties between test formulations and Crinone 8%. Overall, vaginal progesterone gel was well tolerated.